The Effectiveness of Context-Based Experimental Learning in Enhancing Elementary Students’ Problem-Solving Skills on Changes in the States of Matter - Erni Sulistiawati; Irma Dwi Tantri; Abu Dharin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
This study investigates the effectiveness of context-based experimental learning in improving elementary students’ problem-solving skills on the topic of changes in the states of matter. Addressing the persistent gap in Indonesian students’ scientific problem-solving performance reported by PISA 2022, the research employed a one-group pretest–posttest quasi-experimental design involving 18 fourth-grade students from MI Ma’arif NU Cipete. Students’ problem-solving ability defined as the capacity to understand problems, devise strategies, and evaluate solutions was assessed using essay-based tests. The results showed a substantial improvement, with an N-Gain score of 0.72 (high category), indicating strong learning effectiveness. These findings demonstrate that context-based experimental learning not only strengthens conceptual understanding but also fosters active engagement and higher-order thinking skills (HOTS). The study provides empirical evidence supporting this method as a viable instructional strategy in elementary science education. Future research should extend the model to broader topics and diverse school contexts to confirm its generalizability.